RELASI SOSIAL EKONOMI ANTARA PETANI DENGAN TOKEH KELAPA DI KELURAHAN PULAU KIJANG KECAMATAN RETEH KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Nuraini, Nuraini; Majid, Nazori; Agusriandi, Agusriandi (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
Socio-economic relations are everything related to economic actions in meeting community needs such as clothing, food and shelter. In meeting economic needs, a person no longer looks at differences in ethnicity, race or religion. Kijang Island Village is the capital of Reteh District with land used as a coconut plantation by coconut farmers. The phenomenon that occurs is that farmers prioritize selling their harvest to tokeh in Kijang Island Village. This cannot be separated from the influence of a tokeh who is highly trusted by the community so that coconut farmers are very dependent on selling their harvest to the tokeh. The aim of this research is to find out about the socio-economic relations between farmers and coconut tokeh in Pulau Kijang Village, Reteh District, Indragiri Hilir Regency, Riau Province, as well as to find out the cooperative relationship between farmers and coconut tokeh in Pulau Kijang Village, Reteh District, Indragiri Hilir Regency, Riau Province. . In this study the method used was qualitative by checking the validity of the data using triangulation techniques. The results of the research show that the socio-economic relationship between farmers and coconut tokeh occurs because they have the same relationship goals, namely the goal of needing each other's help in buying and selling and receivables and tokeh needs farmers to become regular customers.